Strengthening HIV Education and Health Promotion in Schools: A Case Study of ‘Aisyiyah Junior High School Bantul, Indonesia - Astuti, Dhesi Ari; Saleh, Muhamad; Kurniati, Nurul; Fatimah, Siti; Febrianti, Cindy Putri; Hasibuan, Khoirunnisah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Adolescents are a strategic target in preventing HIV/AIDS and drug abuse. The number of incidences of HIV among children aged 1–14 years has reached 14,150 cases. This number is increased by 700–1,000 each year. In the future, teenagers have the potential to spread information and conducive change, leading society toward a healthier paradigm dealing with HIV/AIDS and drugs. Aims: This recent study is to conduct an assessment of the HIV risks and preventions of HIV at ‘Aisyiyah Junior High School Bantul in order to strengthening HIV education and health promotion in schools. Methods: This research was conducted using a qualitative approach with all the students of Aisyiyah Junior High School Bantul. Focused interviews were conducted to analyze the promotion and prevention of HIV, facilities and infrastructure, access to HIV information, and HIV advocacy in schools. Results: This study highlights several challenges in HIV education at ‘Aisyiyah Junior High School Bantul, Indonesia. Students mostly rely on limited sources like internet articles and school activities for HIV information, but there's a noticeable lack of accessible, comprehensive resources. The school has adequate facilities, including a health unit, but these aren’t being fully utilized for HIV education. While there are some efforts in advocacy, both internal and external, they aren’t as effective as they could be. Overall, the school’s prevention initiatives need more focus and direct engagement with HIV topics, alongside better access to information to truly make a difference. Conclusion: The primary factor in preventing HIV among adolescents is knowledge. Therefore, providing access facilitates infrastructure and makes teenagers the agents of prevention of HIV. In addition, advocacy in the form of promotion and prevention can be conducted. Received: 04 November 2024 | Reviewed: 20 November 2024 | Revised: 15 December 2024 | Accepted: 02 January 2025.